An investigation into the teachers' experiences of workshops on inclusive education as a strategy for professional development in Lebopo Circuit in the Lebowakgomo District, Limpopo Province - Makofane, Inneth Baby (My University, 2019)
The teachers’ workshops seem not to fulfil their designated purpose of equipping educators with proper knowledge of inclusive education. The workshops on inclusive education do not fulfil the purpose of professional development to teachers as one of the goals of the White Paper 6. The purpose of this study was to investigate the teachers’ experiences regarding the workshops on inclusive education as a strategy for professional development in Lebopo Circuit in Lebowakgomo District, Limpopo province. The study followed a qualitative research approach, in which a case study design was applied. Eight teachers who attended inclusive education workshops were purposively selected from four schools in Lebopo Circuit. Data was collected through semi-structured interviews, observations and document analysis. The results of the study indicated that: workshops are impotent to equip educators with adequate knowledge regarding inclusive education; time allocation for conducting workshops is insufficient; there is lack of confidence among the workshop facilitators; and there is lack of support and follow-ups by the provincial Department of Education. The results therefore, imply that the workshops are not effective in equipping educators with knowledge on inclusive education, and they do not serve their purpose as a model of professional development for the teachers. The study suggests that further research should seek to develop the strategies that will improve the quality of workshops on inclusive education, time allocated for workshops, as well as to encourage support and follow-up by the Department of Education.
Thesis (M. Ed. (Curriculum Studies)) -- University of Limpopo, 2019
Keywords: Workshops; Inclusive Education; Professional development; Inclusive education -- South Africa -- Limpopo; Career development -- South Africa -- Limpopo; Educators -- South Africa -- Limpopo